APART BUT TOGETHER - Machnik, Kamila; Wang, Zhaoheng; Li, Zhuoze (My University, 2023)
Vadstena Kommun is a municipality of about 7400 inhabitants in Östergötland County, in southeast Sweden. The current Primary Care Center has about 7,500 listed patients and is located in an older building that is not suitable to modern standards. Therefore, the Region is planning a new building on a new site. The project will contribute to the development of the healthcare regional system towards a "good quality, local health care", which means a modern, equitable, accessible, and effective health care, focusing on primary care. The brief of about 3000 sqm gross area includes a primary care unit, specialist outpatient clinics, public dental care and a child and family health center. The site is within the "Birgitta hospital area", a large area built for different healthcare services since the early 1900s. On the site, one building is planned to be demolished, but another heritage building could be transformed and included as part of the new Primary Care Center.